Brucellosis. - Aleixo, M J (1999)
Brucellosis is a zoonosis, reported for the first time in 1859 by Marston, in Malta. It has also been referred to as Mediterranean Fever, Malta Fever and Bang's disease. Its causative agent was isolated by David Bruce in 1886; this was Brucella melitensis: five different strains were later described: B. abortus, B. suis, B. ovis, B. neotomae and B. canis. Recently, in 1994, the isolation of Brucella was reported in marine mammals, eventually pathogenic to man and unofficially designated "B. maris". Human brucellosis is still a public health problem in countries where the infection has not been eradicated from the animal hosts. When manifested, human disease may assume different courses, widely known, but whose physiopathology is still not totally clear. Much is already known about the agent's molecular biology and in vitro behaviour, but, doubts persist about its in vivo activity, including in human infection. We review some aspects of brucellosis, focusing on the pathogenesis, and referring to new and potential diagnostic methods, therapy and prevention.